From birth till palatoplasty: Prosthetic procedural limitations and safeguarding infants with palatal cleft - Sudhir Bhandari; Bhavita Wadhwa Soni; Shiv Sajan Saini (Wolters Kluwer Medknow Publications, 2018)
The most imminent issue to be addressed in a child born with cleft lip and/or palate is restoration of normal feeding. Early surgical treatment for cleft repair is crucial but may need to be postponed until certain age and weight gain is attained in an infant. When other feeding interventions fail in these children, prosthetic obturation of the defect with feeding instructions in the interim period is indicated to ward off the prevailing concerns. However, the entire prosthetic management presents a significant challenge with respect to the child's age, scope of iatrogenic injury to the delicate oral tissues, and potential for life-threatening situation during the procedures. This article draws attention toward preemptive measures which should be undertaken in the clinical setting during the fabrication of obturator to ascertain a desirable outcome without experiencing a grave complication that may arise due to ignorance and/or lack of facilities.